Potential impacts of solar arrays on regional climate and on array efficiency. (26th January 2017) - Nguyen, Kim C.; Katzfey, Jack J.; Riedl, John; Troccoli, Alberto
ABSTRACT: World population and industrialization have increased significantly, leading to an increase in global energy demand, mainly relying on fossil fuels. Use of alternative energy sources such as wind, hydro and solar has been steadily increasing. Australia is a vast continent which receives an average 58 million PJ of energy from the sun annually. Given this resource potential, one could envisage construction of massive solar farms to help meet energy demands. If such constructions went ahead, their potential benefits/impacts on the climate over and surrounding the solar arrays would need to be investigated. Here, we study the potential climatic impacts over and in the environment surrounding massive hypothetical solar sites across Australia using a global stretched grid atmospheric model. The solar farms are represented by modelling the effects of perturbing surface albedo and surface roughness. The sensitivity experiments incorporate different combinations of surface albedos, shapes and locations of the solar farms, with a focus on the summer season. Our study suggests that depending on array sizes, locations, orientations and surface albedo (potentially increased by means of highly reflective in‐fill material), the climate over solar arrays could be modified significantly. Over the arrays with positive albedo perturbation, rainfall would decrease by around 30–70%, and daytime maximum air temperatures would decrease up to 10 °C. In addition, solar irradiance would increase by around 5–20%, which combined with the air temperature cooling, would lead to an enhanced solar power yield up to 25%.